Treating Hereditary Ataxias—Where Can We Help? - Agarwal, Ayush; Garg, Divyani; Faruq, Mohammed; Rajan, Roopa; Goyal, Vinay; Srivastava, Achal Kumar (Annals of the National Academy of Medical Sciences (India), 2019)
Hereditary ataxias comprise a group of neurological disorders which affect different levels of the neurological axis including the cerebellum, peripheral nerves, cognition, and the extrapyramidal system. These are categorized by the mode of inheritance as autosomal recessive, autosomal dominant, X-linked, and mitochondrial cerebellar ataxia. Definitive curative therapy is not available for these disorders. However, a wide array of emerging treatment options, especially in terms of symptomatic therapy, rescues this group from therapeutic nihilism. Several drugs have been assessed including riluzole, valproate, lithium, etc., as well as rehabilitative, and neuromodulatory strategies. In addition, symptomatic therapies for ancillary symptoms, such as seizures, movement disorders, spasticity, dystonia, etc., should also be targeted. Lastly, molecular therapeutic possibilities are also being explored in animal studies. In this review, we elucidate on the current treatment options available for hereditary ataxias.
Keywords: ataxia; treatable; cerebellar; hereditary ataxia